The Behavior of Patients with Type 2 Diabetes Mellitus in Monitoring Blood Glucose Levels and Foot Care: A Cross-sectional, Community-Based Study - Anita Joeliantina; Jujuk Proboningsih; Hepta Nur Anugrahini; Joylyn L. Mejilla (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Hyperglycemia in patients with Diabetes Mellitus (DM) can lead to complications such as diabetic foot ulcers. Therefore, efforts are needed to prevent this chronic complication through proper foot care. This study aimed to determine the behavior of patients with type 2 diabetes mellitus (T2DM) in performing blood glucose monitoring and correct foot care. This study is a descriptive cross-sectional study, with a sample size of 125 patients with T2DM from the Community Health Center in Surabaya Indonesia. Data was collected with the use of a self-made questionnaire from May to October 2018. The variables of the study were patient characteristics, random blood glucose levels, blood glucose monitoring and foot care skills. The data analysis used was Spearman rho to determine the factors associated with foot care behaviors. Fifty-six percent (56%) of the participants have poor behavior on foot care, 36 % have moderate and only 7.2% have good. Factors that were significantly associated with foot care behavior were signs and symptoms (p = 0.023), blood glucose monitoring (p = .000), and random blood glucose levels (p = 0.040). The behaviors of patients with T2DM in blood glucose monitoring and foot care need to be improved to prevent complications from diabetic foot ulcers. Nurses must provide health education about the importance of regular foot care to patients and their families. The results of this study can be used to further improve the programs and services to prevent DM and delay the progression of chronic complications like diabetic foot ulcers at the community level.